2017
DOI: 10.1101/cshperspect.a026948
|View full text |Cite
|
Sign up to set email alerts
|

DNA Hypomethylating Drugs in Cancer Therapy

Abstract: Aberrant DNA methylation is a critically important modification in cancer cells, which, through promoter and enhancer DNA methylation changes, use this mechanism to activate oncogenes and silence of tumor-suppressor genes. Targeting DNA methylation in cancer using DNA hypomethylating drugs reprograms tumor cells to a more normal-like state by affecting multiple pathways, and also sensitizes these cells to chemotherapy and immunotherapy. The first generation hypomethylating drugs azacitidine and decitabine are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
87
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 126 publications
4
87
0
1
Order By: Relevance
“…5-azacytidine and decitabine have been used to improve survival and health quality of patients with myelodysplastic syndromes (MDS), acute myelogenous leukemia (AML) and chronic myelomonocytic leukemia (CMML) 4 6 . Nonetheless, due to their incorporation into the DNA and the formation of DNA adducts these drugs may have unwanted side effects, limiting their clinical applications 4 , 7 . There is thus need to develop new therapeutic strategies (i.e., new DNMT inhibitors) and to identify biomarkers that may help predict which patient will most benefit from DNMTi therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5-azacytidine and decitabine have been used to improve survival and health quality of patients with myelodysplastic syndromes (MDS), acute myelogenous leukemia (AML) and chronic myelomonocytic leukemia (CMML) 4 6 . Nonetheless, due to their incorporation into the DNA and the formation of DNA adducts these drugs may have unwanted side effects, limiting their clinical applications 4 , 7 . There is thus need to develop new therapeutic strategies (i.e., new DNMT inhibitors) and to identify biomarkers that may help predict which patient will most benefit from DNMTi therapy.…”
Section: Introductionmentioning
confidence: 99%
“…At the transcriptional level, expression of PLBC1 , BCL2L10 or micro-RNA-126 influence the response to DNMTi 18 20 . Furthermore, the efficacy of 5-azacytidine can be further enhanced by combination with other compounds including histone deacetylase inhibitors (HDACi) 1 , 4 , 7 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Decitabine (DAC, 5-aza-2′-deoxycytidine) is a hypomethylating drug currently used for the treatment of myelodisplastic syndrome and is currently gaining much attention for its use in other forms of blood cancer, including acute myeloblastic leukemia (Gardin and Dombret, 2017;Sato et al, 2017), as well as solid cancer (Linnekamp et al, 2017). Recent studies have also shown that DAC possesses potent immunomodulatory properties through different pharmacological mechanisms, that entail induction of regulatory T cells and shift of the Th1-Th17/Th2 cytokine balance, in favor of the latter, with consequential promotion of an anti-inflammatory mileau.…”
Section: Introductionmentioning
confidence: 99%
“…This then results in loss of DNMT1, as the DNA-protein adduct is degraded by the DNA damage response pathway. 9 After loss of haematologica 2019; 104:e138 LETTERS TO THE EDITOR Figure 1. SY-1425 and hypomethylating agents had synergistic antiproliferative activity in RARA-high and IRF8-high cells.…”
mentioning
confidence: 99%
“…A B C DNMT1, the cell cannot maintain its methylation enabling re-initiation of cellular differentiation pathways and induction of proliferative arrest. 5,9,10 We recently demonstrated that super-enhancer (SE) analysis can define novel epigenomic subtypes of non-APL AML. In non-APL AML, RARA pathway activation, detected by the presence of SEs at the RARA or IRF8 gene loci, was found to be predictive of response to SY-1425 in preclinical models, establishing the potential for biomarker-guided clinical studies.…”
mentioning
confidence: 99%